Job burnout among teachers handling English as a foreign language in China: review and prospects - Yu, Qiangfu; Yu, Xiaofeng (Frontiers in Psychology, 2023)
In recent years, job burnout of English as a foreign language (EFL) teachers in China has become prominent in the field of education and psychology, with the related research articles generally on the rise. Using the database of Web of Science (WOS) and the sub-database of Chinese Social Sciences Citation Index (CSSCI) in China National Knowledge Infrastructure (CNKI) database, this paper comprehensively reviews the current situation of research on job burnout of EFL teachers in China between 2020 and 2023, from the aspects of research methods, research focuses and research findings. The literature research results show that on the whole, the research on job burnout of EFL teachers in China is still in its infancy, and that the research level is still relatively low. Based on the systematic reviews of the collected studies, we can conclude that although there is no unanimous conclusion between demographic variables and job burnout severity of EFL teachers in China, we can intervene at both the teacher and school levels to alleviate job burnout of EFL teachers. This review paper analyzes some main problems existing in the current research, for example, lack of theoretical construction and guidance, too much concentration on some research topics, lack of diversified and interdisciplinary research methods, lack of longitudinal research, and potential directions for future research are also discussed in the paper.